2021
DOI: 10.1016/j.cyto.2021.155627
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-17 monoclonal antibodies in hospitalized patients with severe COVID-19: A pilot study

Abstract: Background One of the main pathophysiological mechanisms underlying the severe course of COVID-19 is the hyper-inflammatory syndrome associated with progressive damage of lung tissue and multi-organ dysfunction. IL-17 has been suggested to be involved in hyper-inflammatory syndrome. Objective To evaluate the efficacy and safety of the IL-17 inhibitor netakimab in patients with severe COVID-19. Study design. In our retrospective case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 13 publications
1
35
0
3
Order By: Relevance
“…These wide favorable actions support a protective role of IL-17 inhibitors in COVID-19 [ 32 ]. Very recently, in a pilot case-control study, it was demonstrated that the patients with severe COVID-19 treated with anti-IL-17 monoclonal antibodies showed moderated inflammatory response and improved oxygenation; however, treatment did not seem to improve survival, or reduce mechanical ventilation requirement [ 33 ]. With the aim of achieving new target-specific drug therapies, examining cytokines known to be associated with chronic hyper-inflammatory diseases could potentially lead us in repurposing drugs and improving the existing therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…These wide favorable actions support a protective role of IL-17 inhibitors in COVID-19 [ 32 ]. Very recently, in a pilot case-control study, it was demonstrated that the patients with severe COVID-19 treated with anti-IL-17 monoclonal antibodies showed moderated inflammatory response and improved oxygenation; however, treatment did not seem to improve survival, or reduce mechanical ventilation requirement [ 33 ]. With the aim of achieving new target-specific drug therapies, examining cytokines known to be associated with chronic hyper-inflammatory diseases could potentially lead us in repurposing drugs and improving the existing therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…All treatment-related adverse events were typical for IL-17 inhibitors: neutropenia, lymphopenia, and upper respiratory tract infections. The potential efficacy of netakimab for treating cytokine release syndrome in COVID-19 has been examined in at least two retrospective studies: in comparison with patients who did not receive anti-cytokine therapy or were treated by tocilizumab 57 , and in comparison with SOC therapy including hydroxychloroquine, azithromycin, low-molecular-weight heparins, and corticosteroids 58 . Both studies indicated that netakimab is safe.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 inhibitors did not increase the risk of progressive COVID-19 [108]. For the use of IL-17 antagonists in COVID-19, there are very scarce data, limited to a recent study from Russia, which fail to show clinical benefit of netakimab [109].…”
Section: Anti-il-17 Antagonistsmentioning
confidence: 98%